Droplet digital PCR application for the detection of SARS-CoV-2 in air sample - Rashid, Siti Aishah; Nazakat, Raheel; Muhamad Robat, Rosnawati; Ismail, Rohaida; Suppiah, Jeyanthi; Rajendran, Kamesh; Raj Louis Masalamany, A. S. Santhana; Muhamad Hendri, Nur Afrina; Mohamad, Nadia; Khairul Hasni, Nurul Amalina; Suib, Fatin Amirah; Nik Hassan, Nik Muhamad Nizam; et al. (Frontiers in Public Health, 2023)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) may transmit through airborne route particularly when the aerosol particles remain in enclosed spaces with inadequate ventilation.There has been no standard recommended method of determining the virus in air due to limitations in pre-analytical and technical aspects. Furthermore, the presence of low virus loads in air samples could result in false negatives. Our study aims to explore the feasibility of detecting SARS-CoV-2 ribonucleic acid (RNA) in air samples using droplet digital polymerase chain reaction (ddPCR).Active and passive air sampling was conducted between December 2021 and February 2022 with the presence of COVID-19 confirmed cases in two hospitals and a quarantine centre in Klang Valley, Malaysia. SARS-CoV-2 RNA in air was detected and quantified using ddPCR and real-time reverse transcriptase-polymerase chain reaction (RT-PCR). The comparability of two different digital PCR platforms (QX200 and QIAcuity) to RT-PCR were also investigated. Additionally negative staining transmission electron microscopy was performed to visualize virus ultrastructure. Detection rates of SARS-CoV-2 in air samples using ddPCR were higher compared to RT-PCR, which were 15.2% (22/145) and 3.4% (5/145), respectively. The sensitivity and specificity of ddPCR was 100% and 87% respectively. After excluding 17 negative samples (50%) by both QX200 and QIAcuity, 15% samples (5/34) were found to be positive both ddPCR and dPCR.There were 23.5% (8/34) samples This is a provisional file, not the final typeset article that were detected positive by ddPCR but negative by dPCR. In contrast, there were 11.7% (4/34) samples that were detected positive by dPCR but negative by ddPCR. The SARS-CoV-2 detection method by ddPCR is precise and has a high sensitivity for viral RNA detection. It could provide advances in determining low viral titter in air samples to reduce false negative reports, which could complement detection by RT-PCR.RT-PCR. We also proposed optimized parameters for better sampling and detection of SARS-CoV-2 viruses in air samples.